Resistance of Patriarchal Hegemony in Susan Glaspell’s Trifles - Aryal, Kamana; Panthee, Dinesh (Journal of Tikapur Multiple Campus, 2026)
This paper investigates the theme of female subjugation in Susan Glaspell’s Trifles. The micro-level observations made by women are considered as mere trifles by dismissing them from the legal investigation. Yet, the women eventually succeed in becoming the real heroes through their silent resistance by protecting Minnie. Their common shared experience of suffering enables them to build the strong emotional bond and thus empowering them to uncover the truth which they prefer to conceal from the men only to serve justice. The women’s curious eyes catch the evidence by the moment they enter the house while the superficial men fail to perceive the reality hidden in these apparently irrelevant details. The paper argues that Glaspell critiques the male-centred legal system and reclaims the domestic sphere as a vital site of knowledge, resistance, and ethical judgement to validate how women’s marginalization becomes the actual source of authority and ethical judgement. To authenticate its central argument, this paper draws on the feminist theory of Bell Hooks — that condemns patriarchy and encourages women’s canonical role in literature and society. Bell Hooks’ books The Will to Change: Men, Masculinity, and Love, and Feminist Theory: from margin to centre function as the primary theoretical aspect.